Academic library online services during pandemic covid-19: the experience of Universiti Teknologi MARA, Malaysia / Nurul Farihah Sarmin Panut and Asmahani Abdullah. - Sarmin Panut, Nurul Farihah; Abdullah, Asmahani (Perpustakaan Tun Abdul Razak (PTAR), 2021)
Perpustakaan Tun Abdul Razak (PTAR) in line with Open and Distance Learning (ODL) mode of teaching and learning in UiTM system, has bring out these initiatives with new norms to continuously assist teaching, learning, research and innovation activities among university members. This paper highlights six online library services offered by PTAR during pandemic COVID-19 in Malaysia. Document analysis approach was used to highlight the online library services initiatives. Secondary data is used in this study through the PTAR UiTM Shah Alam official records. This paper is very useful in providing valuable insights and practical solutions in addressing pandemic issues for other academic libraries that facing similar challenges in continuing providing library services to meet the user needs.